Efforts to Overcome Procrastination through Individual Construction Using Self-Introspection Methods in Achieving Santri Scholarship Program Students (PBSB) - Afiyatin, Alfiyah Laila (Journal Intellectual Sufism Research (JISR), 2019)
The purpose of this article is to find out the description of student procrastination and theimplications of counseling individuals with self-introspection techniques to overcomeprocrastination. This research was conducted on seventh semester Santri Achievement ScholarshipProgram (PBSB) students, data collection techniques were carried out by interview and observation.Subjects were 7 students and special subjects for in-depth interviews of 3 students, with the aim ofdeep meaning. The results of the study and discussion are that the general picture of studentprocrastination can be seen from postponement, laziness, and delay. While the impact of theapplication of self-introspection (muhasabah) by students in overcoming procrastination is to reduceprocrastination, which is evident from the following indicators: first consideration before takingaction, careful on activities that are priority, create better change.